1st International Conference on Agriculture, Natural Resources, and Rural Development (ICANaRD) 2021. Issue 1 (November 2021) - Unknown
Abstract: We are very happy to bring you the proceedings of the first International Conference of Agriculture, Natural Resources, and Rural Development (ICANaRD). This conference is intended to maintain knowledge exchange on policy support that allows for improving resource management for agricultural competitiveness towards progressive, self-reliance, and modern agriculture. The theme of 1 st ICANaRD is "Enhancing Agricultural Competitiveness through Better Resource Management for Farmers' Welfare" to address critical issues, innovative methods, and accountable measures to formulate strong policy support for sustainable an inclusive agricultural development. The conference was held virtually on 27-28 July 2021, hosted by the Indonesian Center for Agriculture Socio Economic and Policy Studies (ICASEPS), Ministry of Agriculture. The conference was organized in collaboration with the Indonesian Society of Agricultural Economics (ISAE). Agriculture and rural sector remain to be major economic drivers at which agricultural producers and rural economies need to be supported through appropriate policies. Policy support should allow a fair agricultural product competitiveness, both for local markets and for global trade. With all challenges faced by stakeholders in rural areas, the availability of resources needs to be inclusively managed to meet the right balance between economic growth, poverty reduction, and environmental sustainability. High recognition on this condition would lead to key elements as foundation to recreate appropriate policy, institutional role, and financial support to promote agricultural resource competitiveness for sustainable and inclusive development of rural sector. List of Chair of the Organizing Committee, Editors, Host Organizer are available in this pdf.